PENGARUH AKUNTABILITAS, TRANSPARANSI, DAN KUALITAS PELAYANAN TERHADAP MINAT MUZAKI MEMBAYAR ZAKAT - Nahdliatul Amalia; Tika Widiastuti (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the effect of accountability, transparency, and service quality on the interest of muzaki (study at zakat institutionsSurabaya). This study uses a quantitative approach with multiple linear regression analysis. The population in this study is all muzaki registered at zakat institutions in Surabaya. The sampling technique using convenience sampling. This study uses 6 (six) zakat institutions that have been selected by taking a sample of 120 muzaki. Primary data collection in this study used a questionnaire. Based on the results of the study show that accountability, transparency, and service qualitypartially have a positive and significant effect on the interest of muzaki to paying zakat. Accountability, transparency, and service qualitysimultaneously have a positive and significant effect on the interest of muzaki to paying zakat.Keywords: Accountability, Transparency, Service Quality, Interest, Zakat, Zakat InstitutionREFFERENCESAr Rahman, Muhammad .A.M. (2003).1001 masalah zakat dan solusinya. Jakarta: Pustaka Cerdas Zakat.Hadi, Sutrisno. (1991). Analisis Butir Untuk Instrumen Angket, Tes, dan Skala Nilai. Yogyakarta: FP UGM.Hafidhuddin, Didin. (2002). Zakat Dalam Perekonomian Modern. Jakarta: Gema Insani Press.Jaelani, A.F..(2006). Membuka Pintu Rezeki.Depok: Gema Insani.Lucas, D.B & Britt, S.H. 2003.Advertising Psychology and Research. New York: Mc Graw-Hill.Nurhayati, Sri dan Wasilah. (2009). Akuntansi Syariah di Indonesia.Edisi 2. Jakarta: Salemba Empat.Permono, Sjechul Hadi. (2005). Formula Zakat Menuju Kesejahteraan Sosial. Surabaya: CV. Aulia Surabaya.Sangadji, Etta Mamang dan Sopiah.(2013). Perilaku Konsumen. Yogyakarta: CV ANDI OFFSET.Tapanje, A.M.A. (2009). Corporate Governance From The Islamic Perspective: A  Comparative Analysis With OECD Principles,Critical Perspectives On  Accounting. Vol 20.Undang-undang Nomor 38 Tahun 1999 Tentang Pengelolaan Zakat.